Legal Accountability for Police Members Involved in Narcotics Crimes - Romdoni, Muhamad (IHSA Institute, 2024)
This writing aims to determine the factors that cause Polri members to be involved in narcotics crimes and the legal accountability of individual Polri members who are proven to have committed narcotics crimes. The writing emphasizes normative law, with the data source being secondary data. The conclusions obtained are as follows: First, the factors that cause members of the National Police to be involved in criminal acts are personal, the environment, the economy, and weak internal supervision from the National Police. Second, members of the National Police proven to be involved in narcotics crimes can be held legally accountable through administrative sanctions in the form of dismissal for violating the code of ethics. Criminal liability can be sought in the form of a prison sentence by the provisions of Law Number 35 of 2009 concerning Narcotics.